(untitled) (African Journal of Law and Politics, 2023)
Indigenous peoples have articulated ideas of communal stewardship over their lands, territories and natural resources, regardless of the de jure and de lege lata discrimination and contempt they experience within national States. Notably, their right to survive as ‘a people’, depends on the extent of State recognition of their internationally recognised rights and substantive guarantees under domestic law. In Cameroon, property rights is inherent on the State and subject to statutory regulations to ensure its appropriate, sustainable and fair use. But the complex, superfluous and confusing nature of indigenous tenure under the land and forestry tenures in Cameroon – which falls short of indigenous aspirations - invites a review in line with international standards on indigenous protection. Thus, the focus is to constructively appraise the nature of the existing guarantees on the rights of indigenous people to land and the resources found within their lands and territories in Cameroon.